Conceptual design of a mechatronic system for supporting basic quality of life of bedridden elderly people - Silva, Bruno (2014)
Ambient Assisted Living is an important subject to be explored and developed, especially in developed countries, due to the increasing number of aged people. In this context the development of mechatronic support systems for bedridden elderly people (BEP) living in their homes is essential in order to support independence, autonomy and improve their quality of life. Some basic tasks as eating, taking a bath and/or hygiene cares become difficult to execute, regarding that often the main caregiver is the other element of the aged couple (husband or wife). This paper presents the conceptual design of a mechanical system especially devoted to assist the caregiver in the handling and repositioning of the BEP. Issues as reducing the number of caregivers, to only one, and reducing the system's handling complexity (because most of the time it will be used by an aged person) are considered. The expertise obtained from the visits to rehabilitation centers and hospitals, and from working meetings, are considered in the development of the proposed mechatronic system.